A quasimetagenomics method for concerted detection and subtyping of Salmonella enterica and E. coli O157:H7 from romaine lettuce. (December 2020) - Townsend, Anna; Li, Shaoting; Mann, David A.; Deng, Xiangyu
Abstract: Quasimetagenomics refers to the sequencing of a modified food microbiome to facilitate combined detection and subtyping of targeted pathogens in a single workflow. Through quasimetagenomic sequencing, pathogens are detected and subtyped in a shortened time frame compared to traditional culture enrichment and whole genome sequencing-based analyses. While this method was previously used to detect and subtype Salmonella enterica from chicken, iceberg lettuce, and black pepper, it has not been applied to investigate multiple pathogens in one workflow. A quasimetagenomic method to concertedly detect and subtype Salmonella enterica and Escherichia coli O157:H7 from artificially contaminated romaine lettuce in a single workflow was developed. All quasimetagenomic samples with initial target pathogen inoculum levels of 1 CFU/g were detected and serotyped after co-enrichment of the two pathogens for 12 h. Single nucleotide polymorphism typing was achievable for some initial pathogen inoculum levels as low as 0.1 CFU/g. Our results suggest that this method can be used for concerted detection and subtyping of multiple bacterial pathogens from romaine lettuce even at low contamination levels. Highlights: Concerted detection and subtyping of multiple bacterial pathogens from romaine lettuce at low contamination levels. Much faster turnaround than separated pathogen detection and WGS analysis. This method may expedite traceback and pathogen identification during outbreaks involving a short shelf life commodity.